Asymptomatic hyper-creatine-kinase-emia as sole manifestation of inclusion body myositis - Josef Finsterer; Claudia Stöllberger; Gabor G. Kovacs (MDPI AG, 2013)
Sporadic inclusion body myositis (sIBM) usually manifests with painless weakness of the hand, finger and hip flexors. Absence of symptoms or signs, but mild hyper-CK-emia as the sole manifestation of IBM, has not been reported. We report the case of a 73-year-old male who presented with asymptomatic recurrent hyper-CK-emia ranging from 200 to 1324 U/L (n<171 U/L), since 10 years. Clinical neurologic investigation, nerve conduction studies and EMG were non-informative. Muscle biopsy surprisingly revealed sIBM. sIBM may be asymptomatic and may manifest with hyper-CK-emia exclusively. So, it has to be included in the differential diagnoses of asymptomatic hyper-CK-emia.